2019
DOI: 10.1021/acsbiomaterials.9b00207
|View full text |Cite
|
Sign up to set email alerts
|

Silk-Fibroin-Assisted Cathodic Electrolytic Deposition of Calcium Phosphate for Biomedical Applications

Abstract: The biological responses of artificial biomaterials are affected strongly by its interfacial topography, especially from nano-to microscale. The structure controllability is essential for the design and synthesis of novel biomedical materials. Herein, the effect of soluble silk fibroin (SF) on the cathodic electrolytic deposition (ELD) behavior of octacalcium phosphate (OCP) coating is studied. It is observed that the addition of soluble SF does not change the inorganic phase of the coating (OCP), but it has a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…[ 7–10 ] Among them, silk is a promising biomaterial candidate in BTE due to its remarkable mechanical properties, biocompatibility, biodegradability, low immunogenicity, and ease of fabrication. [ 11–16 ] Increasing studies strengthened the potential of silk‐based BTE materials in bone regeneration ( Figure 1 ). [ 17–21 ] Although several reviews have discussed silk materials in BTE, [ 17–25 ] recent studies revealed the remarkable development of silk BTE substrates with osteogenic capacities.…”
Section: Introductionmentioning
confidence: 99%
“…[ 7–10 ] Among them, silk is a promising biomaterial candidate in BTE due to its remarkable mechanical properties, biocompatibility, biodegradability, low immunogenicity, and ease of fabrication. [ 11–16 ] Increasing studies strengthened the potential of silk‐based BTE materials in bone regeneration ( Figure 1 ). [ 17–21 ] Although several reviews have discussed silk materials in BTE, [ 17–25 ] recent studies revealed the remarkable development of silk BTE substrates with osteogenic capacities.…”
Section: Introductionmentioning
confidence: 99%
“…The widespread use of chitosan is to some extent difficult due to the production of this polysaccharide by using a high-tech method of deacetylation of a chitin biopolymer released from the protective coating of the external organs of various small living creatures, such as crabs, crayfish, fish, pupae, etc. [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%